Stabilization, Debt, and Fiscal Policy in the Caribbean - Sahay, Ratna (IMF Working Papers; Working Paper ;, 2005)
Although Caribbean countries have been largely successful in bringing annual inflation down to single digits in recent years-regardless of their exchange rate regime-their growth rates have been disappointing and their public debt has risen rapidly. By 2003, 14 of 15 Caribbean countries ranked in the top 30 of the world's highly indebted emerging market countries. Most of the increase in their public debt is accounted for by a deterioration in primary fiscal balances that has been largely due to a sharp increase in expenditures rather than a fall in revenues. With the countries of the region now increasingly facing unsustainable debt positions, innovative ways need to be found to raise their economic growth rates and generate fiscal savings to reverse the debt buildup, and to maintain or raise their current living standards.